7(6+x)=6(2+x)

Simple and best practice solution for 7(6+x)=6(2+x) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7(6+x)=6(2+x) equation:


Simplifying
7(6 + x) = 6(2 + x)
(6 * 7 + x * 7) = 6(2 + x)
(42 + 7x) = 6(2 + x)
42 + 7x = (2 * 6 + x * 6)
42 + 7x = (12 + 6x)

Solving
42 + 7x = 12 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
42 + 7x + -6x = 12 + 6x + -6x

Combine like terms: 7x + -6x = 1x
42 + 1x = 12 + 6x + -6x

Combine like terms: 6x + -6x = 0
42 + 1x = 12 + 0
42 + 1x = 12

Add '-42' to each side of the equation.
42 + -42 + 1x = 12 + -42

Combine like terms: 42 + -42 = 0
0 + 1x = 12 + -42
1x = 12 + -42

Combine like terms: 12 + -42 = -30
1x = -30

Divide each side by '1'.
x = -30

Simplifying
x = -30

See similar equations:

| 1/5+y=-7/10 | | 4.07-.61x=.82-5.16x | | -(8-5)-1= | | 3/x-5=4/x+5 | | 3b=1/2r-2m | | 3m+2=25 | | 5m+1=26 | | 0.04x+0.07*(15000-x)=600 | | 5a+5=7+2a | | -1-2-4= | | 8x-9y=3 | | 8x+7=7x | | 2s+2(s+2)=4(s+2)-4 | | x+(-17)=1 | | x*(x+1)/2=453 | | -2y=-8x | | (1/4)-(5/y)=3 | | 7y+4(y-6)=4(y+2)-5 | | p(x)=3x^4-4x^3+x^2+6x-2 | | -2d+8=2(-d+4) | | 3.6x+14.7=.3-1.2x | | .3x+8.6=.65x+10 | | 13-20-(-2)= | | y=-4x^5+2x^4+6x+5 | | 25-2(7+5)= | | 36+35/5*4 | | 4(c-3)-6=6 | | -7(x+2)-18=25+6 | | 141/9-13/18 | | .4+.6x=.53+.5x+1.5 | | 3x^4-4x^3+x^2+6x-2= | | 2x+y=-400 |

Equations solver categories